The Risk Factors Effect of Knee Osteoarthritis Towards Postural Lateral Sway - Muhammad Siddik1, Ratna Darjanti Haryadi1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Osteoarthritis (OA) is the main cause of impairment and disability in elderly. Patient with OA experience progressive functional impairment shown in increasing dependence on walking, using stairs and etc. Patients with OA experience increased static postural sway in the lateral and anteroposterior due to several factors. Objective: This study aims to analize the risk factors of knee osteoarthritis on postural lateral sway. Method: This research is a cross sectional study. The severity of the respondents’ knee OA, unilateral/ bilateral, dominant side, knee joint alignment, body mass index (BMI), and postural lateral sway were measured with Gait Analyzer Peak Motus 2000, and their quadriceps muscle activity was assessed with Myomed. Respondents involved in this study were 38 elderly with unilateral or bilateral knee OA stage 1 until 3 based on the criteria of Kellgren & Lawrence. The data were analyzed with multiple linear regression. Results: The results showed that postural lateral sway was 2.23+0.59 cm. BMI, dominant side, OA types, OA severity, Quadriceps angle, and tibio-fibular angle (TFA) were found with the p value = 0.421, 0.599, 0.780, 0.913, 0.596, and 0.984 respectively. The Visual Analogue Scale (VAS) variable was R Square = 0.291, p = 0.001, Y = 0.3096 and X = 0.9393. Conclusion: Pain is the strongest predictor factor of postural lateral sway disturbances in patients with knee OA.